Edukasi tentang Akhlak Komunikasi di Dunia Industri dan Masyarakat bagi Siswa SMK Fadlun Nafis Bangsri Jepara - Asiyah, Siti; Huda, Nurul (Mafapress Institut Pesantren Mathali'ul Falah Pati, 2024)
In communicating, ethics are very important and necessary so that in addition to the purpose of communication can be conveyed effectively also does not cause problems and even misunderstandings. This service aims to provide education about communication morals in the industrial world and society students of SMK Fadlun Nafis Bangsri Jepara. The service method used is Participatory Action Research (PAR). The results of this service show that SMK Fadlun Nafis students are able to apply communication morals well by being able to communicate or speak softly, speak correctly, be able to speak appropriately and apply manners in communicating.